A Radical Community of Aid: A Rejoinder to Opponents of Affirmative Duties to Help Strangers - Yeager, Daniel B. (1993)
Part One sets forth and criticizes the law of criminal omissions, and considers why bystanders often omit ; that is, fail to intervene on behalf of strangers. Viewing the problem through a well-publicized barroom rape, Part Two presents the minority states' provisions. Part Two also discusses the results of my letter survey of supervising prosecutors in the jurisdictions that have duty-to-aid and duty-to-rescue laws' and analyzes the few cases which have been litigated under these statutes. Part Three attempts to demonstrate that the prevailing law of omissions no longer achieves a desirable balance between the two coveted values of autonomy and security